2021
DOI: 10.1101/2021.01.03.424919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Newcastle disease virus induced ferroptosis through p53-SLC7A11-GPX4 axis mediated nutrient deprivation in tumor cells

Abstract: SummaryA number of new cell death processes have been discovered in recent years, including ferroptosis, which is characterized by the accumulation of lipid peroxidation products derived from iron metabolism. The evidence suggests that ferroptosis has a tumor-suppressor function. However, the mechanism by which ferroptosis mediates the response of tumor cells to oncolytic viruses remains poorly understood. Newcastle disease virus can selectively replicate in tumor cells. We show that NDV-induced ferroptosis ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…In addition, breast cancer cell which exposed to 2DG showed a reduction in total glutathione and elevation in glutathione disulfide and lipid peroxidation (36). Recently, work documented that NDV impedes glutathione synthesis, glutathione peroxidase down-expression, and ROS accumulation in the cancer cells (37). Thus, current results indicate that combination therapy decreases the metabolism of glucose lead to T-GSH depletion and elevation of ROS.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition, breast cancer cell which exposed to 2DG showed a reduction in total glutathione and elevation in glutathione disulfide and lipid peroxidation (36). Recently, work documented that NDV impedes glutathione synthesis, glutathione peroxidase down-expression, and ROS accumulation in the cancer cells (37). Thus, current results indicate that combination therapy decreases the metabolism of glucose lead to T-GSH depletion and elevation of ROS.…”
Section: Discussionmentioning
confidence: 78%
“…The current result showed that combination therapy induces a higher apoptosis rate than NDV alone or 2DG alone. NDV had several mechanisms for inducing apoptosis, including endoplasmic reticulum pathway, ferroptosis, caspase-dependent and caspase-independent pathways (28,37,39). In addition, 2DG induces ER stress-induced apoptosis by protein N-glycosylation disrupting (40).…”
Section: Discussionmentioning
confidence: 99%